Persepsi Guru-guru Bahasa Melayu di Sekolah Jenis Kebangsaan Daerah Port Dickson, Negeri Sembilan terhadap Penguasaan Kemahiran Lisan Bahasa Melayu Sepanjang Pandemik COVID-19 (Jurnal Bahasa, 2022)
Mastery of listening and speaking skills (oral) in Malay language is a major problem in Teaching and Learning (PdP) in schools. Moreover, teachers who teach Malay mostly have no option. This problem became more serious when the COVID-19 pandemic hit the world. Can teachers teach oral skills virtually? A study was conducted to identify the perceptions of teachers who teach the mastery of Malay oral skills to non-native speaking students throughout the Teaching and Learning at Home (PdPR) period. A total of 101 teachers participating in the Malay Language Knowledge Sharing Program virtually were selected as respondents. They consisted of teachers who teach Malay in 16 Chinese National Type Schools (SJKC) and 17 Tamil National Type Schools (SJKT) in Port Dickson District, Negeri Sembilan. The study was conducted using a quantitative design. The research instrument used was a questionnaire that was adapted, containing 34 items using the 5-point Likert scale feedback and semi -structured questions. The data were supported by interviews with 4 teachers and one SISC+ officer from Port Dickson District. The discussion is based on the Behaviourism Theory. The data obtained were analyzed using Statistical Package for the Social Sciences (SPSS) Version 25.0 using descriptive statistics. The findings showed that the perception of teachers who implemented PdPR in this new norm is encouraging. Various initiatives and sacrifices have been made by the teachers at SJK to continue the PdP of students throughout the COVID-19 pandemic that hit the world. The impact of the program is expected to improve the performance of Malay language in SJK after the face-to-face classes are conducted again.Keywords:Listening and speaking skills, Home Teaching and Learning (PdPR), vernacular school, perception, COVID-19 pandemic, virtual teaching and learningFull text: PDF